“PRAGMALINGUISTICS AS A MODERN SUBFIELD OF LINGUISTICS” (Journal of Universal Science Research, 2025)
The study explores pragmalinguistics as a modern field of linguistics, its theoretical foundations, and the role it plays in understanding how people use language in specific communicative contexts. We examine key concepts such as speech acts, politeness strategies, and the influence of culture and society on language use. Furthermore, the study highlights the growing significance of pragmalinguistics in contemporary linguistic studies, offering insights into its applications in language teaching, translation, and cross-cultural communication.